Pengaruh Metode Pembelajaran Karya Kelompok Terhadap Keterampilan Proses Sains Dengan Kovariabel Kemampuan Berpikir Kreatif Siswa Pada Mata Pelajaran Biologi - Theodora Sarlotha Nirmala Manu; Fransina Th. Nomleni (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The purpose of this research is to determine: (1) the difference of the science process skills of students learning using group workshop method with students using the discussion method; (2) differences in the condition above, after the ability of creative thinking covariable is controlled; and (3) the contribution of creative thinking covariable towards the science process skills of students. This experimental research used the post-test only control group design, with the population of 210 students of grade XI SMA Negeri 7 Kota Kupang. The total samples were 140 students, distributed in 2 experimental classes and 2 control classes. The data was collected by observing the science process skills using creative thinking skill test. The data were analyzed in descriptive and inferential statistics using one-way covariance analysis (Anacova). The result indicated that: (1) there was a significant difference of science process skills between the students learning using the group workshop method with students learning using the discussion method with an F value of 50,964; p ≤ 0.05.; (2) Having controlled the student’s creative thinking ability, there was a significant difference between student’s science process skills among students who enrolled in group workshop method with the students enrolled in the discussion method; where F=17.822; p ≤ 0,05. (3) Creative thinking ability contributed to the science process skills with the coefficient of determination equals to r2=(0,430)2 = 0,185 or 18,5%. The results indicate that the application of group workshop methods has positive effect on improving students' science process skills and creative thinking skills.